Cardiosphere-Derived Cells and Ischemic Heart Failure. Issue 1 (January 2018) - Ashur, Carmel; Frishman, William H.
Abstract : After a myocardial infarction, heart tissue becomes irreversibly damaged, leading to scar formation and inevitably ischemic heart failure. Of the many available interventions after a myocardial infarction, such as percutaneous intervention or pharmacological optimization, none can reverse the ischemic insult on the heart and restore cardiac function. Thus, the only available cure for patients with scarred myocardium is allogeneic heart transplantation, which comes with extensive costs, risks, and complications. However, multiple studies have shown that the heart is, in fact, not an end-stage organ and that there are endogenous mechanisms in place that have the potential to spark regeneration. Stem cell therapy has emerged as a potential tool to tap into and activate this endogenous framework. Particularly promising are stem cells derived from cardiac tissue itself, referred to as cardiosphere-derived cells (CDCs). CDCs can be extracted and isolated from the patient's myocardium and then administered by intramyocardial injection or intracoronary infusion. After early success in the animal model, multiple clinical trials have demonstrated the safety and efficacy of autologous CDC therapy in humans. Clinical trials with allogeneic CDCs showed early promising results and pose a potential "off-the-shelf" therapy for patients in the acute setting after a myocardial infarction. The mechanism responsible for CDC-induced cardiac regeneration seems to be a combination of triggering native cardiomyocyte proliferation and recruitment of endogenous progenitor cells, which most prominently occurs via paracrine effects. A further understanding of the mediators involved in paracrine signaling can help with the development of a stem cell–free therapy, with all the benefits and none of the associated complications.